2016
DOI: 10.14260/jemds/2016/1102
|View full text |Cite
|
Sign up to set email alerts
|

Ct Evaluation of Diseases of Paranasal Sinuses

Abstract: BACKGROUNDDiseases of paranasal sinuses include wide-spectrum ranging from inflammatory condition to neoplasm. CT has replaced conventional radiographs as imaging modality of choice for assessment of paranasal sinus diseases. In present study, thirty patients were taken for evaluation by CT referred by ENT Dept. The examination of paranasal region by CT was tailored according to individual clinical problem, covering overall area to make the study anatomically complete. This study proved good results of CT eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…13 Ranjan et al conducted a study on 30 cases with age ranging from 8 yrs to 68 yrs and maximum incidence in the 2 nd decade. 14 Kandukuri et al reported maximum disease incidence in 2 nd and 3 rd decade in their study of 50 patients. 15 The incidence of sinonasal disease is found to be more in males which may be due to the more prevalence of these diseases among males or merely a reflection of the overall higher male attendance in the hospital, illiteracy and lack of health consciousness among the females.…”
Section: Discussionmentioning
confidence: 90%
“…13 Ranjan et al conducted a study on 30 cases with age ranging from 8 yrs to 68 yrs and maximum incidence in the 2 nd decade. 14 Kandukuri et al reported maximum disease incidence in 2 nd and 3 rd decade in their study of 50 patients. 15 The incidence of sinonasal disease is found to be more in males which may be due to the more prevalence of these diseases among males or merely a reflection of the overall higher male attendance in the hospital, illiteracy and lack of health consciousness among the females.…”
Section: Discussionmentioning
confidence: 90%